Hepatocyte nuclear factor 3 beta contains two transcriptional activation domains, one of which is novel and conserved with the Drosophila fork head protein. - Pani, L (1992)
The hepatocyte nuclear factor 3 (HNF-3) gene family is composed of three proteins (alpha, beta, and gamma) that are transcription factors involved in the coordinate expression of several liver genes. All three proteins share strong homology in their DNA binding domains (region I) and are able to recognize the same DNA sequence. They also possess two similar stretches of amino acids at the carboxyl terminus (regions II and III) and a fourth segment of homology at the amino terminus (region IV). Furthermore, the HNF-3 proteins demonstrate homology with the Drosophila homeotic gene fork head in regions I, II, and III, suggesting that HNF-3 may be its mammalian homolog. In order to define HNF-3 beta protein domains involved in transcriptional activation, we have used a reporter gene, whose transcription is dependent on HNF-3 binding, for hepatoma cell cotransfection assays with expression vectors that produced different truncated HNF-3 beta proteins. A position-independent activation domain which contained conserved regions II and III was identified at the carboxyl terminus of the HNF-3 beta protein (amino acids 361 to 458). Moreover, site-directed mutations that altered the sequences within regions II and III demonstrated their importance to transactivation. The region II-III domain does not possess amino acid sequences in common with other transcription factors and may define a novel activation motif. HNF-3 beta amino-terminal sequences defined by conserved region IV also contributed to transactivation, but region IV activity required the participation of the region II-III domain. Region IV is abundant in serine amino acids and contains two putative casein kinase I phosphorylation sites, a feature similar to protein motifs described for the transcription factors Pit-1/GHF-1 and HNF-1.